“Los costos de producción de los productos agrícolas y su incidencia en la rentabilidad de los productores de la parroquia de Cubijíes en el año 2015” - Buenaño Pesántez, María Isabel (2017)
The present research developed entitle "The costs of production of agricultural products and their impact on the profitability of the producers in a parish called Cubijíes during the year 2015", was elaborated with the objective of determining the factors that influence in the costs of production and know the costs of the productive cycle, of the main agricultural products that are grown in that parish through the application of the hypothetical deductive method since the problem was formulated, the hypothesis was created, the results were analyzed and interpreted obtained from the application of the instruments such as the survey and the interview, and finally the hypothesis was verified. An analysis of the production costs of white corn flour was carried out, in which a cost of $ 1,287.90 was determined for a production of 160 sacks, obtaining a profit margin of 36%, on the other hand, the cost of production of a potato called Cecilia established a total cost of $ 3,447.00 for a production of 280 sacks reaching a profit margin of 30%. Finally, a broccoli cultivation manual based on production costs was proposed to establish the selling price and improve the profitability of the agricultural producers from Cubijíes.